SELECTED ASPECTS OF MARTIAL ARTS FOR HEALTH UNDERLYING THEIR PRO-ACTIVE INFLUENCE IN THE CONTEXT OF CENTRAL NERVOUS SYSTEM PLASTICITY - Gora, Tomasz; Spałek, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of this study is to extend the knowledge of selected aspect of  of taekwon-do (martial art)  for health in the context of central nervous system plasticity.  This paper aims at presenting the results of the research and concepts that contribute to the understanding of the value of development and teaching of taekwon-do and other martial arts in the context of the notion of contact. The research data indicate that there are substantial arguments that allow us to state that participation in martial arts  is strictly connected with an integrated activity in different fields of child’s and adolescent’s development. In the case of adults (included patients with musculoskeletal chronic pain) it supports the functioning of the nervous system.  Based on the research approach specified as neuroscience, one can interpret the research reports present in literature, that indicate positive changes in particular brain structures, involved, among others, in the ability to concentrate, as a result of  this training.